Reliability enhancement of software programs by minimizing the overflow errors - Garnaik, Shrija; Gayen, Tirthankar; Mishra, Samaresh (International journal of system assurance engineering and management, 2014)
Reliability is always important in all systems but sometimes it is more important than other quality attributes, especially in mission critical systems where the severity of consequence resulting from failure is very high. Hence, it is important to develop comprehensive techniques for developing reliable software. But, it is found that there exist no suitable model to enhance the reliability of software for diverse operating environment and also it is difficult to develop a fully reliable software for all applications. Considering these aspects this paper proposes an effective approach to enhance the reliability of software by minimizing the overflow errors caused during the execution of any program.